β-meso-Fused pyrene–porphyrin scaffolds with panchromatic absorption features - Oleszak, Christoph; Ritterhoff, Christian; Meyer, Bernd; Jux, Norbert (Organic & Biomolecular Chemistry, 2024)
The π-extension of porphyrins with pyrenes through the β-mesofusion of five-membered rings is demonstrated. Three architectures resulting from combining up to two porphyrins and pyrenes were obtained straightforwardly in good overall yields. Although significantly planarized, the molecules retain excellent solubility and processability. Spectroscopic characterization and density-functional theory calculations reveal intriguing absorption features.
CRIS-Team Scopus Importer:2025-02-04